Political Dividends of Digital Participatory Governance : Evidence from Moscow Pothole Management - Gorgulu, Nisan (World Bank, Washington, DC, 2020)
This study takes advantage of a publicly salient policy sphere -- road quality -- in the Russian Federation's capital city to explore the use of digital technologies as means of aggregating information and demonstrating government capacity and effectiveness. It focuses on the potential linkage between road quality based on citizens' complaints and electoral outcomes in two rounds of Moscow mayoral elections in 2013 and 2018. The data on more than 200,000 online potholes’ complaints were collected and combined with local election data. The causal relationship between these two processes is established, making use of an arguably exogenous variation in the differences across local weather conditions during the heating season that differentially affects pothole creation but is uncorrelated with electoral outcomes. The results indicate that greater use of digital technologies (measured by pothole complaints) results in an increased number of votes and a higher margin of victory for the incumbent. They highlight digital technologies' role as a tool to create participatory governance mechanisms and convey to the public an image of a transparent, responsive, and capable government.